Origins of wind‐driven intraseasonal sea level variations in the North Indian Ocean coastal waveguide. Issue 21 (15th November 2013) - Suresh, I.; Vialard, J.; Lengaigne, M.; Han, W.; McCreary, J.; Durand, F.; Muraleedharan, P. M.
Abstract [1] In this paper, we show that a linear, continuously stratified ocean model reproduces observed wind‐driven intraseasonal sea level variability in the coastal waveguide of the Northern Indian Ocean (NIO). Sensitivity experiments with intraseasonal wind forcing selectively applied in the equatorial region, Bay of Bengal, and Arabian Sea show that a large part of the basin‐scale sea level variations are driven by zonal wind fluctuations along the equator. Within the NIO coastal waveguide, the contribution of remote equatorial forcing decreases from ~80–90% in the Andaman Sea to ~50% northeast of Sri Lanka and then increases to ~60–70% along the west coast of India. During the southwest monsoon, intraseasonal wind variations become stronger over the NIO, resulting in a larger contribution of local wind forcing to sea level variability along the west (up to 60%) and east (up to 40%) coasts of India.